THE LIGHTHOUSE MOVIE: DOMINATION, SUBJUGATION, AND EXPLOITATION - Mulyadi Hoar; Christy Tisnawijaya (Department of English Literature, Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
Power relations is a compelling and complex social issue that has been present throughout human history. It is just as prominent in today’s day and age as in every period of human life; it is also represented in movies. The Lighthouse movie, written and directed by Robert Eggars (2019), depicts the life of two lighthouse keepers, a supervisor and his assistant. They get stranded on a remote island off the coast of New England in the 1890s when a massive storm hits the island. Left with only alcohol as their emergency food supply, the power balance between supervisor and assistant worsens. This article is a film study; the film was analyzed by examining the narrative and cinematography elements. The discussion consults Michel Foucault’s theory (1982) regarding power relations, how power works, the forms they take, and how it is imposed. The finding shows that the supervisor exercises power through domination, subjugation, and exploitation of the assistant. As the setting of the place, the lighthouse has a symbolic meaning of power; as it navigates the ships on the sea, the lighthouse keeper rules what happens both inside and outside his house.